Case Checking of the External Head in Relative Clauses - Talat Masood (Social Science Review Archives, 2025)
The primary goal of this paper is to find out case checking of the external nominal in relative clauses. The secondary goal of this paper is to determine the suitability of the three standard theories for the structure of relative clauses for explaining case checking in relative clauses. This study involves taking examples from different languages and analyzing them for morphological case forms and case checking. This study establishes that in majority of cases the morphological case forms of the external nominals in relative clauses correspond to the case forms of the main clause and not the relative clause. This corroborates the standard view that case to the external nominal of a relative clause is assigned from outside the relative clause. As a consequence of this substantiation, the relative suitability of the three theories for relative clauses, namely, matching analysis, raising analysis, and head-external analysis, is determined. The study establishes that the matching analysis and head-external analysis are more suited to explain case checking in external nominals of relative clauses.